+0  
 
0
79
3
avatar

What is the exact form and corrected to three decimal places if not an integer of ln (x^2-1)-ln(x-1)=ln6

Guest Feb 17, 2017
Sort: 

3+0 Answers

 #1
avatar
0

Solve for x:
log(x^2 - 1) - log(x - 1) = log(6)

log(x^2 - 1) - log(x - 1) = log(1/(x - 1)) + log(x^2 - 1) = log((x^2 - 1)/(x - 1)):
log((x^2 - 1)/(x - 1)) = log(6)

Cancel logarithms by taking exp of both sides:
(x^2 - 1)/(x - 1) = 6

Multiply both sides by x - 1:
x^2 - 1 = 6 (x - 1)

Expand out terms of the right hand side:
x^2 - 1 = 6 x - 6

Subtract 6 x - 6 from both sides:
x^2 - 6 x + 5 = 0

The left hand side factors into a product with two terms:
(x - 5) (x - 1) = 0

Split into two equations:
x - 5 = 0 or x - 1 = 0

Add 5 to both sides:
x = 5 or x - 1 = 0

Add 1 to both sides:
x = 5 or x = 1

log(x^2 - 1) - log(x - 1) ⇒ log(1^2 - 1) - log(1 - 1) = (undefined)
log(6) ⇒ log(6) ≈ 1.79176:
So this solution is incorrect

log(x^2 - 1) - log(x - 1) ⇒ log(5^2 - 1) - log(5 - 1) = log(2) + log(3) ≈ 1.79176
log(6) ⇒ log(6) ≈ 1.79176:
So this solution is correct

The solution is:
Answer: |x = 5

Guest Feb 17, 2017
 #2
avatar+79894 
0

ln (x^2-1) - ln(x-1) = ln(6)      write as

 

ln [ (x^2 - 1) / (x - 1) ]  =  ln 6     we can forget the logs

 

(x^2 - 1) / (x - 1)  = 6     rearrange

 

x^2 - 1  =  6 (x - 1)  simplify

 

x^2 - 1  = 6x - 6

 

x^2 - 6x +  5  = 0     factor

 

(x - 1) ( x -5) = 0    set each factor to 0    and x  = 1  [reject because it makes one or more logs undefined]  or x  = 5  which is valid..

 

 

 

cool cool cool

CPhill  Feb 17, 2017
 #3
avatar
0

I wonder if we can do it this way?

ln(x^2-1) - ln(x-1) = ln 6

ln ( (x^2-1)/(x-1) ) = ln 6

ln  [ (x-1)(x+1)/(x-1) ] = ln 6

ln  (x+1)  = ln 6

x+1 = 6

x = 5

Guest Feb 17, 2017

19 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details